Analysis of Gait Disturbance in Glut 1 Deficiency Syndrome. (November 2016) - Blumenschine, Michelle; Montes, Jacqueline; Rao, Ashwini K.; Engelstad, Kristin; De Vivo, Darryl C.
Anticipating potential therapies for Glut 1 deficiency syndrome (Glut1DS) emphasizes the need for effective clinical outcome measures. The 6-minute walk test is a well-established outcome measure that evaluates walking ability in neurological diseases. Twenty-one children with Glut 1 deficiency syndrome and 21 controls performed the 6-minute walk test. Fatigue was determined by comparing distance walked in the first and sixth minutes. Gait was analyzed by stride length, velocity, cadence, base of support, and percentage time in double support. Independent sample t -tests examined differences between group. Repeated-measures analysis of variance evaluated gait parameters over time. Glut 1 deficiency syndrome patients walked less ( P < .05), had slower velocities ( P < .0001), had shorter stride lengths ( P < .0001), spent more time in double support ( P < .001), and had increasing variability in base of support ( P = .009). Glut 1 deficiency syndrome patients have impaired motor performance, walk more slowly, and have poor balance. The 6-minute walk test with gait analysis may serve as a useful outcome measure in clinical trials in Glut 1 deficiency syndrome.